P.157L: Late News Poster: Characterization of Asymmetrical Negative Bias Stress Effect on the Density‐of‐States and Parasitic Resistances in a‐IGZO Thin‐Film Transistors. Issue 1 (1st July 2013) - Jo, Chunhyung; Bae, Hagyoul; Jun, Sungwoo; Choi, Hyunjun; Hwang, Seonwook; Kim, Dae Hwan; Kim, Dong Myong; Ahn, Byung‐Du; Lee, Je‐Hun; Song, Junho
Abstract The dominant mechanism of the negative bias stress (NBS)‐induced instability is investigated not to be a change in the subgap DOS but a change in the parasitic resistance caused by the reduced Schottky barrier of the metal contacts. This was verified by the extracted source/drain resistance and TCAD simulation.